UPAYA PENINGKATAN PRODUKSI KEDELAI (Glycine max Merr.) SEBAGAI UPAYA MENINGKATKAN KEUNTUNGAN PETANI DI JAWA TIMUR - Hendri Widonoto; M. Zainul Arifin (University of Jember, 2008)
The aim of this research were (1) to understand the application of technology in Glycine max Merr farming in The Jember and Banyuwangi Regency, (2) to understand the Glycine max Merr farming efficiency and (3) to understand the factors that influencing Glycine max Merr production. The data was collected from the farmer in Jember and Banyuwangi regency. The data was analyzed by descriptive and inference analysis using one sample t-test, R/C ratio and Cobb-Douglass production function. The result shows that there is difference between the average value (-20,23) of application technology in Glycine max Merr farming and the fix average (285,80), the R/C ration is less than one, and the influencing factors to Glycine max Merr production are land area, employee, fertilizer, pesticides, dummy of location, dummy of technology. Key word : rising production, technical efficiency, R/C ratio